2008
DOI: 10.1002/ffj.1872
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and characterization of volatile extracts of Capsicum annuum L. and Allium spp.

Abstract: The aroma extracts were identi¼ed by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). The major aroma compounds of the plant extracts were sulphides, alcohols and heterocyclic compounds. Antioxidant activities of the aroma extracts were evaluated using two different assays. The aroma extracts isolated from green pepper, Welsh onion, onion and garlic inhibited the oxidation of hexanal by 51%, 95%, 96% and 98%, respectively, for 1 month at a level of 500 mg/ml; these extracts inhibited m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 18 publications
(18 reference statements)
1
15
0
1
Order By: Relevance
“…In GC-MS analysis, we found that WRFE contained different volatile components and active phenolic compounds, which may have varying antioxidant and antimicrobial activities (Jang et al, 2008;Strobel et al, 2001). The major aroma constituents of WRFE were 1-butanol, dodecyl acrylate and cyclododecane, which constituted more than 60% of the total amount of volatiles (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…In GC-MS analysis, we found that WRFE contained different volatile components and active phenolic compounds, which may have varying antioxidant and antimicrobial activities (Jang et al, 2008;Strobel et al, 2001). The major aroma constituents of WRFE were 1-butanol, dodecyl acrylate and cyclododecane, which constituted more than 60% of the total amount of volatiles (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…This area, mostly run by local small-scale farmers, is famous for its top-quality, fragrance-rich green onions. Green onions and garlic are commonly consumed vegetables that possess markedly bioactive potentials, such as antioxidant capacity [4], antimicrobial activity [5,6], antiplatelet activities [7] and anticancer activity [8]. With successful demonstration of the functioning properties of the Sunshin green onions, this study would help the local farmers to market their produce with value adding strategies and benefit economically from their production.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols and quercetin in plants have been reported to be the major compounds exhibiting antioxidant activity [4,9]. In addition, the antioxidant activity of quercetin and its functional effects have been fully demonstrated in a few previous studies [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Among the several small molecules retained in plants, polyphenols (hydrolysabletannins/phenylpropanoids) are the most abundant antioxidants in our diet and have been shown to play a possible role in the prevention several chronic diseases (Bravo, 1998;Hotta et al, 2002;Gosslau et al, 2011b). Polyphenol antioxidants, such as resveratrol, inhibit the occurrence and/or growth of mammalian tumors (Jang et al, 2008), and a wide variety of phenolic substances derived from plants have been shown to display marked antioxidant and anti-infl ammatory activities, gallic acid and volatiles (1-butanol, dodecyl acrylate and cyclododecane), displayed a broad range of anti-oxidant, antimicrobial and anti-allergic effects Joo et al, 2010). In the present study, we examined the anti-infl ammatory properties of the hexane fraction from the white rose fl ower, which may be used as a natural source of bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%